An investigation of flux characteristic in direct torque control using sector rotation strategy - Siti Azura A. Tarusan; Auzani Jidin; Mohd Luqman M. Jamil; Kasrul Abdul Karim (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Stator flux fails to regulate at low operating speed condition is a common drawback for the conventional direct torque control (DTC). It is due to the inevitable of zero-voltage vector demagnetization that interrupts the controlling of stator flux in DTC. Hence, a fixed sector rotation strategy is one of the solutions to rectify the raised issue. The strategy is based on the decreasing stator flux droop, which is an easy technique to change the sector of flux locus at a specific angle. However, this strategy only focuses at low operating speed. Thus, the stator flux droop effect at the various speed needs to be analysed. In this paper, an investigation is conducted by using simulation (MATLAB/Simulink) and experimental setup (dSPACE board) where a good agreement has been achieved between the predicted and measured results. The analysis taking into account between the conventional method (without strategy) and the proposed method (with strategy). In conclusion, the influence of stator flux droop is inversely proportional to the operating speed.